23 Response of newly weaned pigs to commercial eubiotic acid product or zinc oxide supplementation following enterotoxigenic Escherichia coli (K88) challenge. (7th December 2018) - Hossain, M; Owusu-Asiedu, A; Hall, H; Al-Juobori, A; Nyachoti, C
Abstract: Post-weaning diarrhea caused by enterotoxigenic Escherichia coli K88 (ETEC), continues to be a major challenge in nursery pigs. The study compared bioefficacy of commercial Eubioitc acid product containing formic and propionic acids (pHorce TM ) with zinc oxide in piglets, following oral challenge with ETEC. A total of 48 newly weaned piglets were randomly assigned to 1 of 4 treatments with 6 replicates pens (2 pig/pen) per treatment. Treatments were; unchallenged control; no additives (UC), challenged control; no additive (NC), NC + eubioitc acid (3 g/kg; EA) and NC + zinc oxide (3 g/kg; ZO). Basal diets were formulated to meet NRC, 2012 recommended nutrient requirements. Each pig was gavaged with 6 mL (6.1 × 10 9 cfu/mL) ETEC solution on d 8 post-weaning. Diarrhea scores (1–5) and rectal temperatures were measured at regular intervals. On d 14 and 28, 1 pig/pen was sacrificed to obtain liver, spleen and digesta samples. Body weight (BW), daily feed intake (ADFI), weight gain (ADG) and gain to feed ratio (G:F) were determined. Data was analyzed as complete randomized design. From d 14 to 28, ADG and G:F improved ( P < 0.10) for pigs fed diets containing ZO and EA compared with NC. Final BW, overall (d 1 to 28) ADG and G:F were 17.8, 16.4, 18.3 and 17.8 kg ( P = 0.19), 0.451, 0.396, 0.457 and 0.450 kg/d ( P = 0.22) and 0.833, 0.692, 0.797 and 0.781 ( P = 0.01) for UC, NC, EA and ZO, respectively. Dietary treatment did not affect ( P > 0.10) diarrhoea score, body temperature, fecal and digesta pH throughout the experimental period. In conclusion, the current study suggests that dietary supplementation of the Eubiotic acid product containing specific combination of formic and propionic acid performed similarly to zinc oxide following enterotoxigenic Escherichia coli K88 challenge in weaned pigs.